Shipping and ship recycling related oil pollution detection in Çandarlı Bay (Turkey) using satellite monitoring. (1st September 2019) - Eronat, Atilla Hüsnü; Bengil, Fethi; Neşer, Gökdeniz
Abstract: Çandarlı Bay is a marine environment at risk of heavy pollution because of industrial facilities including the only ship recycling zone of Turkey, and intense marine traffic related to the raw materials needs of a dense industrial zone. These risk factors make the development of practical environmental management strategies increasingly necessary. Oil spills from the heavy ship traffic, one of the major risks, can be detected by satellite remote sensing technologies. In this study, it is aimed to show spatial characteristics of oil spills as well as its dynamics in the time domain of the bay. Results from a three year period of the study show that as a main environmental problem, oil pollution has a relatively high percentage of spatial distribution in the bay. It is therefore concluded that regular monitoring of the intense oil pollution in the bay is required with an agile and low-cost method of satellite monitoring to intervene in good time and to minimize its impacts. The study provided an extensive understanding of spatio-temporal dynamics of oil pollution in the bay. The approach used will also provide a baseline for decision-makers to develop environmental management plans for other coastal zones with similar sensitivities. Highlights: Çandarlı Bay (Turkey), as a sensitive marine environment, is under the severe oil pollution impact due the activities of the petrochemical and shipping industries including ship recycling. To monitor the oil pollution sources and their effects to the marine environment, the Synthetic Aperture Radar (SAR) has been proposed as a tool. Time series of SAR images data were used to evaluate spatial and temporarily changes of oil pollution in the bay.